Efektivitas Penggunaan Aluminium Foil Terhadap Perubahan Suhu Cairan Ringer Laktat 390C pada Paparan Suhu 250C - Rahmaniyah, Barkatur; Wahid, Abdurahman; Lestari, Dhian Ririn (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Trias of death is a complication between acidosis, hypothermia, and coagulopathy which causes death inhemorrhagic shock. Therefore, it is necessary to take appropriate treatment such as giving 390C warm fluidresuscitation intravenously. This study analyzed the effectiveness of the use of aluminium foil on temperaturechanges of 390C ringer lactate at the exposure of 250C temperature. This study used a pre-experimentalmethod with intact group comparison design, with 4 fluids ringer lactate which was divided into two groups,the control group and the experiment group were warmed up to 390C, and the temperature drop was measuredfor 25 minutes. Data were analyzed using the Mann Whitney test. Statistical results using the Mann-Whitneytest, obtained a p-value of 0, 000. With the value (p-value 0,000 <α = 0.05), it can be concluded that there is asignificant difference in temperature changes between the ringer lactate that were not coated with aluminumfoil and the ringer lactate that were coated with aluminum foil. Total temperature drop for each group were3,1 0C for ringer lactate that were not coated with aluminium foil, and 2,50C for ringer lactate that were coatedwith aluminium foil. The temperature changes of aluminium foil coated ringer lactate which flowed for 25minutes were only 2,50C, this happened because aluminium foil is a thermal insolator that is able to maintainand prevent heat loss. More research about the use of aluminum foil needs to be done with more or differenttypes of layers.